Pengaruh penggunaan akun kuliner di Media Instagram Terhadap Pola Makan Siswa SMK Negeri 2 Binjai - Nasution, Ernawati; Ardiani, Fitri; Aritonang, Evawany Y. (TROPHICO: Tropical Public Health J., 2024)
Today's adolescent food consumption is inseparable from the eating habits of the adolescents themselves and the ease of access to food. The number of technological media that offer food through culinary accounts such as instagram, YouTube, WhatsApp, and others makes it easy to access the food offered on these media. The population in this study were students of SMK Negeri 2 Binjai with a sample size of 205 people. Data on the use of culinary accounts on instagram media which includes duration and frequency and student eating patterns were collected by means of interviews using the food recall form and the food frequency form. The research results show that199 people (97.1%) students whose types of food are not diverse. This non-variety food consumption was more common among female students at SMK Negeri 2 Binjai. The duration of using culinary accounts on instagram media in the low category is 126 (61.5%). However, the frequency of using culinary accounts on instagram is high, namely 107 (52.2%). The results of the Chi Square test also showed that there was a significant relationship between the duration of using culinary accounts on instagram media and students' eating patterns that were not good (p<0.05). Multivariat analysis also shows that there is a significant effect on the duration and frequency of using culinary accounts on instagram media on students' eating patterns that are not good. The variables that influence student eating patterns are the duration and frequency of using instagram media quinary accounts.